Isothermal modelling of the adsorption of Lead(II) onto an antarctic sea-Ice Bacterial Exopolysaccharide - Ubana, Muhammed Abdullahi; Ya'u, Murtala; Marbawi, Hartinie; Yasid, Nur Adeela; Shukor, Mohd Yunus (Hibiscus Publisher, 2022)
The biosorption of the biosorption of lead(II) onto an Antarctic sea-ice bacterial exopolysaccharide is remodeled using nonlinear regression and the optimal mode was determined by a series of error function assessments. The Sips model performed best in statistical tests including root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), accuracy factor (AF), and corrected Akaike Information Criterion (AICc) which is not the same to the originally published work using a linearized form where the Langmuir and Freundlich models best represent the biosorption and the maximum biosorption capacity. The calculated Sips parameters kS (l/g) value of 0.10 (95% confidence interval from 0.08 to 0.13), a maximum monolayer adsorption capacity qmS (mg/g) value of 252.88 (95% C.I. from 222.13 to 283.64) and nS (Sips model exponent) value of 1.16 (95% C.I. from 1.34 to 1.98). This study indicates that a different isotherm model can be obtained using nonlinear regression compared to the popular linearized form that may give relatively inaccurate outcome.